CCAFS Engagement and Communications Strategy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The CGIAR Research Program on Climate Change, Agriculture And Security (CCAFS) is a 10-year strategic partnership of the CGIAR and Future Earth. CCAFS seeks to overcome the threats to agriculture and food security in a changing climate, exploring new ways of helping vulnerable rural communities adjust to global changes in climate. CCAFS partners with all 15 CGIAR centers and challenge program. This cross-center and cross-challenge program initiative creates outstanding communications opportunities and heralds a new way of working in the CGIAR. The goal for CCAFS Engagement and Communications is: To promote a food secure world through the provision of science based efforts that support sustainable agriculture and enhance livelihoods while adapting to climate change and conserving natural resources and environmental services. The objectives of CCAFS engagement and communications are: To provide a credible and authorative platform for scientific information, knowledge and tools on agriculture and food security under climate change. To engage actively at all levels to facilitate user-driven research, science-based dialogue, knowledge sharing, and evidence-based policy, among key partners.